왜 외식소비자들은 페이스북에 후기를 작성하는가?: 후기작성 동기와 그 동기가 기억재구성으로 인해 끼친 인식변화에 대한 고찰 - 노정희; 전수현; Noh, Jeonghee; Jun, Soo Hyun (한국콘텐츠학회 논문지, 14(8), 2014)
As the online word-of-mouth(WOM) using SNS has significant influence on consumer decision-making, the hospitality industry including the restaurant industry has actively used SNSs as one of major marketing tools. While researchers have focused on impacts of the online WOM, there is little research on motivations to provide WOM and its impacts on the WOM providers. The purpose of this study is to examine whether sharing the restaurant experience on Facebook, the representative SNSs, can change customer satisfaction and intentions to revisit and recommended and whether the type of motivations to share the restaurant experiences on Facebook affects customer satisfaction and intentions to revisit and recommend. The total of 260 college students volunteered to participate in this study. They first visited a restaurant and completed surveys twice before and after sharing their restaurant experience on Facebook. According to the study results, the levels of satisfaction, intention to revisit and intention to recommend after sharing the restaurant experience were found to be higher than before sharing the experience. This study also found that people who shared their restaurant experience for nostalgia were more likely to be satisfied with the restaurant services and have a higher level of intentions to revisit and recommend the restaurant. Theoretical and managerial implications as well as limitations and future research directions are discussed. SNS를 이용한 온라인 구전의 중요성과 파급력은 날로 커지고 있으며, 이를 마케팅 도구로 활용 하려는 외식업체들의 관심도 매우 높아지고 있다. 본 연구의 목적은 외식 소비자들이 외식업체를 방문하고 서비스를 체험 한 후 온라인 구전의 역할을 하는 방문후기를 대표적인 SNS인 페이스북에 작성하는 동기에 따라 방문후기 작성 전과 후의 소비자가 지니는 서비스에 대한 만족도, 재방문의사, 추천의사가 후기작성 동기에 영향을 받는지를 살펴보는 것이다. 이를 위해 대학생 260명을 대상으로 외식업체 방문 후 만족도, 재방문의사와 추천의도를 조사하고 페이스북에 후기를 작성한 이후의 만족도, 재방문의사와 추천의도의 차이를 재조사하여 비교하였다. 연구결과 후기작성 후에 느끼는 만족도, 재방문의사, 추천의사가 모두 후기를 작성하기 전보다 높은 것으로 나타났다. 또한, 만족도, 재방문의사, 추천의사의 변화에 영향을 미치는 후기작성 동기 중 추억추구 동기가 다른 후기 작성 동기 보다 전반적으로 영향을 크게 미치는 것으로 나타났다. 이러한 연구결과가 시사하는 이론적, 실무적 의미와 연구의 한계점을 논의하였다.